Korelasi antara Waktu, Ruang, dan Energi dalam Penguatan Ketahanan Energi Nasional - Herman Agustiawan (Jurnal Maksipreneur, 2011)
This paper attempts to bring up the sense of vital energy in people's lives. Without a thorough planning, energy could lead a problem to wildlife as a country's energy security and also could threaten the national security of countries concerned. Choosing a source of energy for at least three factors that must be observed, namely security of supply, pricing (economical price), and the environment that are closely associated with the dimension of time and space.